Ability of pulmonary function decline to predict death in amyotrophic lateral sclerosis patients. Issue 7 (2nd October 2017) - Enache, Irina; Pistea, Cristina; Fleury, Marie; Schaeffer, Mickael; Oswald-Mammosser, Monique; Echaniz-Laguna, Andoni; Tranchant, Christine; Meyer, Nicolas; Charloux, Anne
Abstract: Objectives : Objectives were to evaluate the relative risk of death associated with lung function decline in patients with amyotrophic lateral sclerosis (ALS), and to examine the ability of ALS patients to perform volitional pulmonary function tests (PFTs). Methods : The PFTs of 256 consecutive patients referred to the Strasbourg University Hospital ALS Centre over an eight-year period were reviewed. Slow vital capacity (VC), maximal inspiratory and expiratory pressures (MIP, MEP), sniff nasal inspiratory pressure (SNIP), and peak cough flow (PCF) were performed at diagnosis and then every four months. The instantaneous risk of death associated with PFTs deterioration was calculated using time-dependent covariate Cox models. The changes of each PFT over time were examined and compared. Results : A total of 985 acceptable PFT sessions were recorded. The risk of death was significantly associated with the decline in pulmonary function, regardless of the PFT parameter and its expression. When VC, MIP/SNIP and MEP (% of predicted) decreased by 10%, or PCF decreased by 50 L/min, the risk of death was multiplied by 1.31 (95% CI 1.21–1.41), 1.48 (1.32–1.66), 1.54 (1.32–1.79), and 1.32 (1.19–1.75), respectively. MIP, SNIP and MEP were decreased earlier in the course of disease and plunged deeper than VC within months before death, but were more affected by learning effect. Conclusions : This study provides tools to calculate the increase in risk of death from a PFT decline. At an individual level, since each test showed some flaws, the use of a combination of PFTs for ALS respiratory monitoring is recommended.